2007
DOI: 10.1128/aac.00452-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities of 217 Clinical Isolates of Zygomycetes to Conventional and New Antifungal Agents

Abstract: We evaluated the in vitro susceptibilities of 217 zygomycetes to amphotericin B, ketoconazole, fluconazole, itraconazole, voriconazole, posaconazole, caspofungin, and flucytosine. The significant in vitro activity of posaconazole against several species appears to support its reported clinical efficacy. Decreased susceptibility to amphotericin B was noted with Cunninghamella bertholletiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
187
2
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(229 citation statements)
references
References 28 publications
21
187
2
13
Order By: Relevance
“…Livio Pagano, 1 Oliver A. Cornely, 2,3 Alessandro Busca, 4 Morena Caira, 1 Simone Cesaro, 5 Cristiana Gasbarrino, 6 Corrado Girmenia, 7 Werner J. Heinz, 8 Raoul Herbrecht, 9 Cornelia Lass-Flörl, 10 Annamaria Nosari, 11 Leonardo Potenza, 12 Zdenek Racil, 13 1-2011-2012).…”
Section: Letters To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Livio Pagano, 1 Oliver A. Cornely, 2,3 Alessandro Busca, 4 Morena Caira, 1 Simone Cesaro, 5 Cristiana Gasbarrino, 6 Corrado Girmenia, 7 Werner J. Heinz, 8 Raoul Herbrecht, 9 Cornelia Lass-Flörl, 10 Annamaria Nosari, 11 Leonardo Potenza, 12 Zdenek Racil, 13 1-2011-2012).…”
Section: Letters To the Editormentioning
confidence: 99%
“…[1][2][3] Among the available antifungals, amphotericin B (AmB) formulations and posaconazole demonstrate the most promising in vitro activities against Mucorales, 4,5 and their combination displays synergistic in vitro activity. 6,7 However, pre-clinical studies in neutropenic and diabetic ketoacidotic mice with IM reported no improvement in survival under a combination of posaconazole and liposomal amphotericin B (LAmB), compared to L-AmB monotherapy.…”
mentioning
confidence: 99%
“…Studies have shown in vitro susceptibility to anti-fungal agents to vary within the zygomycetes family and thus, identification of the species provides clues for optimization of treatment. 4 Thus, molecular assays were developed to identify specific species of zygomycetes. These include sequencing of internal transcribed spacer (ITS) region, [5][6][7][8] 28S rRNA 9 and non-sequencing based tests like polymerase chain reaction (PCR) with restriction fragment length polymorphism (RFLP), 10,11 real-time PCR using melting curve analysis, 12 multiplex PCR using specific DNA probes in a microarray based assay, 13 and PCR assay using the Luminex xMAP hybridization method.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to Aspergillus species, which are typically susceptible to voriconazole, amphotericin B, and echinocandins, Mucorales are usually susceptible only to amphotericin B and less frequently to posaconazole (1). Furthermore, there is significant variability in susceptibility by genus; in a study of 217 clinical isolates of Mucorales, 100% of Lichtheimia spp.…”
mentioning
confidence: 99%